2013
DOI: 10.18632/oncotarget.1424
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer stem-like cells with induced translineage-differentiation capacity and are suppressed by alkaline phosphatase inhibitor

Abstract: Spheroid formation is one property of stem cells—such as embryo-derived or neural stem cells—that has been used for the enrichment of cancer stem-like cells (CSLCs). However, it is unclear whether CSLC-derived spheroids are heterogeneous or whether they share common embryonic stemness properties. Understanding these features might lead to novel therapeutic approaches. Ovarian carcinoma is a deadly disease of women. We identified two types of spheroids (SR1 and SR2) from ovarian cancer cell lines and patients' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…We then assessed TET1 expression in OCSCs, and their differentiated progenies, in our previously established OCSC model . Our data showed that TET1 expression levels were increased in OCSCs but decreased in OCSC progeny cells (Figure E,F).…”
Section: Resultsmentioning
confidence: 89%
“…We then assessed TET1 expression in OCSCs, and their differentiated progenies, in our previously established OCSC model . Our data showed that TET1 expression levels were increased in OCSCs but decreased in OCSC progeny cells (Figure E,F).…”
Section: Resultsmentioning
confidence: 89%
“…15 After quantile normalization, log 2transformed values were used to select for most significantly differentially expressed genes, based on genes with their RefSeq categories (with NM_ accession prefix). 15 After quantile normalization, log 2transformed values were used to select for most significantly differentially expressed genes, based on genes with their RefSeq categories (with NM_ accession prefix).…”
Section: Differential Gene Expression Analysis Of Ovarian Spheroidsmentioning
confidence: 99%
“…15 Elucidating the difference between stem (SR-I) and progenitor (SR-II) ovarian HGSC cells may further our understanding of CSCs biology and lead to novel therapies. Targeting CSCs with translineage capability suggests that targeting their territory at a higher hierarchy, may provide opportunities to overcome the bottleneck.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of stem cell markers, response to therapy, and best system for in vivo analysis needs to be conducted between different methods for generating/selection of CSCs. It has been suggested that there are different types of CSCs with different expression patterns of stem cell markers and different prognosis for patients [10][11][12] , thus further definition of what type of CSCs are generated by this protocol may help determine how they relate to human malignancy. Finally, in order to rigorously demonstrate that the CSCs isolated from this protocol are definitive CSCs, cells need to be injected into immunocompromised mice in a limiting dilution assay.…”
Section: Discussionmentioning
confidence: 99%